Nuts about groundnuts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Groundnut By R Schilling & R Gibbons, Tropical Agriculturalist series, co-published by Macmillan CTA ICRISAT CIRAD, 2002. 156 pp. ISBN 0 333 72365 1 CTA number 1091. 10 credit points